Quantum enhanced classical sensor networks - Simmons, D; Coon, J; Datta, A (Institute of Electrical and Electronics Engineers, 2018)
The quantum enhanced classical sensor network consists of K clusters of Ne entangled quantum states that have been trialled r times, each feeding into a classical estimation process. Previous literature has shown that each cluster can ideally achieve an estimation variance of 1/N2e r for sufficient r. We begin by deriving the optimal values for the minimum mean squared error of this quantum enhanced classical system. We then show that if noise is absent in the classical estimation process, the mean estimation error will decay like Ω (1/KN2e r). However, when noise is present we find that the mean estimation error will decay like Ω (1/K), so that all the sensing gains obtained from the individual quantum clusters will be lost.